Developing Suitable Rice-Soya fermented Preparation - Binila Paul (Department of Home Science, College of Agriculture, 1997)
A study on "Developing suitable rice-soya fermented preparation" details a comprehensive information on the advantages of preparing idli, in which blackgram dhal was replaced either by soyabean or by defatted soyaflour. Soaking time, grinding conditions, temperature and fermentation time were kept uniform to study the influence of the food ingredients used on the quality of the product. Thirteen formulations were standardised after making variations in the proportion of b l ac kg r am dhal (from 5 per cent to 30 per cent).